2010
DOI: 10.1007/s10126-010-9330-y
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Up-regulation of Genes Encoding Protein Degradation Enzymes and Heat Shock Protein 90 for Intertidal Green Macroalga Ulva fasciata Against Hypersalinity-Induced Protein Oxidation

Abstract: The molecular acclimation of intertidal green macroalga Ulva fasciata Delile to high salinity stress were examined by the construction of a forward cDNA library via the suppressive subtractive hybridization between 30‰ and 90‰ (24 h) and by the time course dynamics of several abundantly expressed genes. Among the genes with known sequences, the expressed sequence tags are abundant in the function of protein synthesis (ribosomal protein) and destination. The cDNAs of ATP-dependent Clp protease (UfClpC), 20S pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The present results together with our previous study (Sung et al. ) have demonstrated that the acclimation of U . lactuca to hypersalinity stress could be partly achieved by the expression of genes related to protein destination and synthesis for the degradation of damaged and misfolded proteins and for the synthesis of proteins involved in the metabolic regulation and structural adjustment of functional properties.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The present results together with our previous study (Sung et al. ) have demonstrated that the acclimation of U . lactuca to hypersalinity stress could be partly achieved by the expression of genes related to protein destination and synthesis for the degradation of damaged and misfolded proteins and for the synthesis of proteins involved in the metabolic regulation and structural adjustment of functional properties.…”
Section: Discussionsupporting
confidence: 91%
“…lactuca (Sung et al. ). Not only the loss of damaged protein removal but also the loss of correct protein folding after prolonged hypersalinity treatment caused the recovery growth to decrease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations